Rural Development - Contemporary Issues and Practices 2012
DOI: 10.5772/45787
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Conflict Between Farmers and Herdsmen – Implications for Agricultural and Rural Development in Nigeria

Abstract: Land is probably the most important resource needed by Man for his day-today existence. All human livelihoods and activities are directly or indirectly dependent on land at varying thresholds. But land connotes different meanings to the various user groups. For instance, builders, manufacturers, fishermen, miners, hunters and farmers have different specifications in their requirement for land for their production/services. Out of all user groups, agricultural production perhaps exhibits the highest form of sop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…This obvious competition over commons has led to frequent cases of conflict, resulting in loss of human lives and valuable property (Audu, 2014; West Africa Network for Peace Building (WANEP), 2019; Sunday Orji, 2019). Other social ills such as reprisal attacks on humans, cattle rustling, rape, theft and kidnapping, among others (Adisa, 2012;Ofuoku, 2009;Sangotegbe et al, 2015;Tonah, 2000) have been reported as secondary consequences. While the cause of the social ills may have been associated more with the transhumant pastoralist groups, their settled counterparts, many of whom have co-habited peacefully with the indigenes, are not completely insulated from resultant public rage and backlash.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This obvious competition over commons has led to frequent cases of conflict, resulting in loss of human lives and valuable property (Audu, 2014; West Africa Network for Peace Building (WANEP), 2019; Sunday Orji, 2019). Other social ills such as reprisal attacks on humans, cattle rustling, rape, theft and kidnapping, among others (Adisa, 2012;Ofuoku, 2009;Sangotegbe et al, 2015;Tonah, 2000) have been reported as secondary consequences. While the cause of the social ills may have been associated more with the transhumant pastoralist groups, their settled counterparts, many of whom have co-habited peacefully with the indigenes, are not completely insulated from resultant public rage and backlash.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This perception has been on since the Jihad of Sokoto caliphate and so they have been at loggerhead and hence can be engaged in conflict with slightest provocation. More broadly, other scholars report that climate change, the migration further south, growth of agro-pastoralism, expansion of farming on pastures, invasion of farmlands by cattle, assault on non-Fulani women by herders, blockage of stock routes and water points, freshwater scarcity, burning of rangelands, cattle theft, inadequate animal health care and disease control, overgrazing on fallow lands, defecation on streams and roads by cattle, extensive sedentarisation, ineffective coping strategies, ethnic stereotyping, and the breakdown of conflict intervention mechanisms are the root causes of such violence in rural areas (Ofuoku and Isife, 2009;Adekunle and Adisa, 2010;Blench, 2010;Odoh and Chigozie, 2012;Solagberu, 2012;Audu, 2013;Bello, 2013;McGregor, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The farmers around this region who focus on shifting cultivation and rotation of land for fallowing reasons and good output of farm inputs see the invasion of fallowing grounds and other farmlands by the herder"s cattle as direct incursion on their livelihood (Abass, 2012;Akevi, 2014;Durojaiye, 2014). Scholars (Folami 2009; Ofuoku and Isife 2009; Adekunle and Adisa 2010;Blench 2010;Odoh and Chigozie 2012;Solagberu 2012;Audu 2013Audu , 2014Bello 2013;McGregor 2014;Fabiyi and Otunuga, 2016), had identified climate changes as the root cause of farmersherdsmen conflicts over resource use in Nigeria. It was observed by Gefu and Kolawole (nd) that, while some conflicts arise between same resource group such as between one farming community and another, others occur between different user groups such as between herders and farmers or between foresters and farmers.…”
Section: Climate Change Altered Landscapes and Resource Conflictsmentioning
confidence: 99%
“…These literature rest on the untested assumption that the mechanism behind the temperatureconflict link is that disruption of agricultural production provokes local violence. In Nigeria, the growth of agro-pastoralism, the expansion of farming on pastures, the invasion of farmlands by cattle, assault on non-Fulani women by herders, blockage of stock routes and water points, freshwater scarcity, burning of range lands, cattle theft, inadequate animal health care and disease control, overgrazing on fallow lands, defecation on streams and roads by cattle, ethnic stereotyping, and the breakdown of conflict intervention mechanisms, these are usually identified by scholars as the root causes of farmers /herders conflicts (Folami, 2009;Ofuoku and Isife 2009;Adekunle and Adisa 2010;Blench 2010;Odohand Chigozie 2012;Solagberu 2012;Audu 2013Audu , 2014Bello 2013;McGregor 2014). In line with this, Abass (2012) contends that the major source of tensions between pastoralists and farmers is basically economic, with land related issues accounting for the majority of the conflicts.…”
Section: Climate Change and Conflicts Over Land Usementioning
confidence: 99%